Vivir en la calle. El derecho a la vivienda en la jurisprudencia del TSJC - Gargarella, Roberto (2011)
In this essay, two recent decisions of the Buenos Aires City Superior Court\nconcerning the local executive public policies as to "the homeless" access to housing\nwill be critically examined. By discussing the government measures described in these\ncases, broader questions on constitutional theory will arise, such as court control in the\nsocial rights' field, the legal nature of international conventions on human rights and\nthe contradictions between judicial activism and democracy